RESPONS MASYARAKAT TERHADAP STRATEGI KJKS BMT NU GAPURA SUMENEP DALAM MENGURANGI KETERGANTUNGAN PADA RENTENIR - Al-Hadi, Abu Azam; Fitriyah, Faizatul (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam UIN Sunan Ampel Surabaya, 2014)
This research data was compiled by using interview techniques and documentation. Furthermore, the data that has been collected is analyzed using descriptive analysis method, which is a method of describing and interpreting the data that has been collected using inductive mindset. The results of this research concluded that the existence of interesting strategies applied by KJKS BMT NU Gapura Sumenep turned out to be able to reduce the reliance of society against loan sharks. The strategy that is carried out by means of product innovation, service which is easy and convenient, and socialization. These strategies become the differentiating factors between KJKS BMT NU with the moneylenders. In practice of the moneylenders, if the borrower cannot afford the repayments, the interest expenses continue to grow so that it can be troublesome to the borrower. While KJKS BMT NU encourages customers to give some favors, for example by Qardlul Hasan. In the provision of services to communities in need of capital, KJKS BMT NU applies different from other institutions which is very administrative in giving loans to people who need venture capital. If the person is capable and responsible for developing his business, from the results of the interview, KJKS BMT NU will give venture capital loans according to needs and abilities of the applicant. Another strategy is the socializing done KJKS BMT NU form silaturrahim between officers of NU, both branches and twigs, with the aim of disseminating the existence of financial institutions that serve to prosper the people's economy. So many clients claimed to be pleased with the presence of KJKS BMT NU because many helps by developing effort through venture capital loan.